Atom Transfer Radical Polymerization: Billion Times More Active Catalysts and New Initiation Systems. Issue 1 (30th October 2018) - Ribelli, Thomas G.; Lorandi, Francesca; Fantin, Marco; Matyjaszewski, Krzysztof
Abstract: Approaching 25 years since its invention, atom transfer radical polymerization (ATRP) is established as a powerful technique to prepare precisely defined polymeric materials. This perspective focuses on the relation between structure and activity of ATRP catalysts, and the consequent choice of the initiating system, which are paramount aspects to well‐controlled polymerizations. The ATRP mechanism is discussed, including the effect of kinetic and thermodynamic parameters and side reactions affecting the catalyst. The coordination chemistry and activity of copper complexes used in ATRP are reviewed in chronological order, while emphasizing the structure–activity correlation. ATRP‐initiating systems are described, from normal ATRP to low ppm Cu systems. Most recent advancements regarding dispersed media and oxygen‐tolerant techniques are presented, as well as future opportunities that arise from progressively more active catalysts and deeper mechanistic understanding. Abstract : Progressively more active copper catalysts and more benign initiating systems have been designed and applied in 25 years of atom transfer radical polymerization. This review presents the historic development of ligands and initiating systems, which has allowed reduction of the catalyst loading to a few ppm, expansion of the monomer scope, and fine‐tuning of the process.